ISLAMIC SOCIAL REPORTING, KOMISARIS INDEPENDEN, DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN: PERAN MODERASI KINERJA KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI JII TAHUN 2019-2021 - Namira Kamiliya; Aliamin Aliamin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to determine and analyze the effect of Islamic social reporting, independent commissioners, and environmental performance on firm value with financial performance as a moderating variable in companies listed at JII during the 2019-2021 COVID-19 period. The population in this study were all companies listed on the Jakarta Islamic Index during the COVID-19 period 2019-2021. The sample selection used purposive sampling technique with predetermined criteria in order to obtain a sample of 39 companies. The research conducted is quantitative research with the type of research data, namely secondary data. Data analysis used multiple linear regression analysis and moderated regression analysis with the help of SPSS 23 data processing application. The results of this study indicate that either simultaneously or partially the variables Islamic social reporting, independent commissioners, and environmental performance have no effect on firm value and the interaction of financial performance. reflected by Return On Equity (ROE) is not able to strengthen the influence of Islamic social reporting, independent commissioners, and environmental performance on firm value.